2022
DOI: 10.1021/acscatal.2c01128
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Valorization of Poly(ethylene terephthalate) Plastic and CO2 for Simultaneous Production of Formic Acid

Abstract: The electro-reforming of polymer plastic waste and CO2 has the merits for producing value-added chemicals and alleviating environmental pollution. Herein, we report an electrocatalytic integrating strategy for efficient valorization of poly­(ethylene terephthalate) (PET) plastic and CO2 to simultaneously produce formic acid at both anode and cathode. The NiCo2O4 electrocatalyst displays a high Faradaic efficiency of 90% for formic acid production, which indicates the excellent selectivity for PET hydrolysate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 40 publications
2
124
1
1
Order By: Relevance
“…Duan et al reported that EG can be converted into isolable potassium diformate using a CoNi 0.25 P electrocatalyst; 28 and Zhao et al demonstrated that electrocatalysts (CuO and NiCo 2 O 4 ) can catalyze EG into formate. 29,30 Our group also reported that EG can be converted into carbonate by a Pd-based catalyst. 27 However, Pd-based catalysts are relatively expensive and afflicted with poor electrochemical stability.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Duan et al reported that EG can be converted into isolable potassium diformate using a CoNi 0.25 P electrocatalyst; 28 and Zhao et al demonstrated that electrocatalysts (CuO and NiCo 2 O 4 ) can catalyze EG into formate. 29,30 Our group also reported that EG can be converted into carbonate by a Pd-based catalyst. 27 However, Pd-based catalysts are relatively expensive and afflicted with poor electrochemical stability.…”
Section: Introductionmentioning
confidence: 93%
“…25,26 Recently, electrochemical reforming of PET into addedvalue and separable chemicals has been proposed. [27][28][29][30] PET can be hydrolyzed into terephthalate (TPA-K) and ethylene glycol (EG) monomers when catalyzed under basic conditions. Unfortunately, the subsequent separation of the products requires equipment for a more demanding distillation process and energy input due to the high boiling point (197.6 °C), viscosity (19.8 mPa s at 20 °C) and excellent water solubility of EG.…”
Section: Introductionmentioning
confidence: 99%
“…This work showcases the processing design for plastic upcycling and displays structure–catalytic activity correlation studies by leveraging electrocatalytic techniques in electrooxidation of biomass derivatives. Further development of advanced electrocatalysts and integration with upstream photovoltaic generation are currently in progress. Moreover, integrating anodic plastic reclamation with CO 2 reduction shows the merits of increasing economic value of products and alleviating environmental pollution …”
Section: Electrochemical Processes For Plastic Upcyclingmentioning
confidence: 99%
“…Electrocatalytic oxidative valorization of PET waste hydrolysate has also been integrated with CO 2 reduction reactions (CO 2 RRs) toward simultaneous production of formic acid at both the anode and cathode through the following equations: By the use of a low-cost NiCo 2 O 4 nanowire on carbon fiber paper as the anodic catalyst and a SnO 2 nanosheet on carbon cloth as the cathodic catalyst, this reaction system can trigger electrocatalytic PET valorization and CO 2 RR in one system. A homemade electrolyzer was made that achieved a total FE for formic acid of 155%.…”
Section: Electrochemical Processes For Plastic Upcyclingmentioning
confidence: 99%
See 1 more Smart Citation